2017
DOI: 10.4209/aaqr.2016.04.0154
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional View of Atmospheric Aerosols over an Urban Location in Central India

Abstract: Surface, column and vertically resolved variations of physical and optical properties of atmospheric aerosol over Hyderabad, a tropical urban location in central India are explored on the basis of ground based and satellite retrieved data. Annual mean aerosol optical depth (τ) observed with Microtops sun-photometer is 0.61 ± 0.07 and seasonally it varied from 0.71 ± 0.06 in pre-monsoon to 0.55 ± 0.05 in winter. Aerosol types are categorized based on Ångström exponent (α) and τ relations; revealed that the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
(44 reference statements)
0
0
1
Order By: Relevance
“…In this paper, we compared the BC mass concentration of JSR and RNC with other cities of India. The mean BC mass concentration reported at JSR (15.87 μgm −3 ; Present study) was found to be higher as compared to Agra 29 9.5 μgm −3 , Ahmedabad 30 8.3 μgm −3 ; Dhanbad 11 6.5 μgm −3 ;, Guwahati 31 7.2 μgm −3 , Hyderabad 32 9.7 μgm −3 , Visakhapatam 33 4.8 μgm −3 , Kolkata 34 5.0 μgm −3 , Ranchi 35 8.5 μgm −3 ; New Delhi 36 17.4 μgm −3 , Patana 37 9.1 μgm −3 , Pune 38 13.8 μgm −3 , Srinagar 39 6.0 μgm −3 , Tirupati 40 1.0 μgm −3 , Varanasi 35 μgm −3 ;Present study). And BC concentration reported at present study sites (JSR and RNC) was found to be low as compared to Kharagpur 33 21.0 μgm −3 , National Capital Territory 41 33.9 μgm −3 and Raipur 42 23.0 μgm −3 .…”
Section: Comparison Of Bc Mass Concentration At a Different Locationcontrasting
confidence: 43%
“…In this paper, we compared the BC mass concentration of JSR and RNC with other cities of India. The mean BC mass concentration reported at JSR (15.87 μgm −3 ; Present study) was found to be higher as compared to Agra 29 9.5 μgm −3 , Ahmedabad 30 8.3 μgm −3 ; Dhanbad 11 6.5 μgm −3 ;, Guwahati 31 7.2 μgm −3 , Hyderabad 32 9.7 μgm −3 , Visakhapatam 33 4.8 μgm −3 , Kolkata 34 5.0 μgm −3 , Ranchi 35 8.5 μgm −3 ; New Delhi 36 17.4 μgm −3 , Patana 37 9.1 μgm −3 , Pune 38 13.8 μgm −3 , Srinagar 39 6.0 μgm −3 , Tirupati 40 1.0 μgm −3 , Varanasi 35 μgm −3 ;Present study). And BC concentration reported at present study sites (JSR and RNC) was found to be low as compared to Kharagpur 33 21.0 μgm −3 , National Capital Territory 41 33.9 μgm −3 and Raipur 42 23.0 μgm −3 .…”
Section: Comparison Of Bc Mass Concentration At a Different Locationcontrasting
confidence: 43%